Human Bite-induced Cellulitis Due to Streptococcus pyogenes - (:unkn) unknown (My University, 2015)
The rate of infection after a human bite is 10%-30%. Streptococcus spp. are the most common pathogens that may cause serious infections, such as necrotizing fasciitis. The authors describe a 5-year-old girl admitted to the emergency room with cellulitis due to S. pyogenes after human bites. She presented with fever and pain in her left arm, and her medical history revealed a human bite by her cousin on the arm 3 days prior. The wound culture yielded S. pyogenes. She was successfully treated with intravenous ampicillin-sulbactam regimen. S. pyogenes may cause serious wound infections following human bites. In such cases, the patient should be closely followed. Chemoprophylaxis should be initiated in an appropriate clinical setting to prevent secondary bacterial infections. This case was first reported as cellulitis due to S. pyogenes after a human bite.
Keywords: Female; Humans; Treatment Outcome; Child, Preschool; Streptococcal Infections; Anti-Bacterial Agents; Arm; Streptococcus pyogenes; Bites, Human; Amoxicillin-Potassium Clavulanate Combination; Cellulitis